If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2 = -2(x + 7) Reorder the terms: 2 + 2x = -2(x + 7) Reorder the terms: 2 + 2x = -2(7 + x) 2 + 2x = (7 * -2 + x * -2) 2 + 2x = (-14 + -2x) Solving 2 + 2x = -14 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2 + 2x + 2x = -14 + -2x + 2x Combine like terms: 2x + 2x = 4x 2 + 4x = -14 + -2x + 2x Combine like terms: -2x + 2x = 0 2 + 4x = -14 + 0 2 + 4x = -14 Add '-2' to each side of the equation. 2 + -2 + 4x = -14 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = -14 + -2 4x = -14 + -2 Combine like terms: -14 + -2 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 200+0.15x=332 | | n+17=12 | | 8x+5=5x-7 | | 4x-4=4x-1-2 | | 6(3x+2)+5(4x+3)= | | 2x+3y=9.5 | | 5(x+7)=70 | | 108=473+23h | | 6-p2/8=-4 | | x-9+4x+5+5x-=50 | | 19x+29=105 | | 100(y^3z^2/5x)^2 | | 7x+5=2(4x+3) | | .5x-3.=.2x-.5 | | -188-7x=8x+17 | | (-6-x)/(3x-12)=0 | | 4/9+3/7 | | (x-5)*(1/2)-(2*x-1)*(1/3)=6 | | h+1/4h=35 | | 64d^2-36/8d+6 | | x+7/3=10 | | 64d^2-36/8d | | 1/3+5/12x-2=62/3 | | x^4+4x^3-19x^2-46x-1200=0 | | 2k^2-(12k+1)x+12=0 | | 8x5/2-88=0 | | tanx=-0.4 | | 3x+4+x=4x+1+3 | | 4(5x-3)=12(x+1) | | 1.7(2.7)3x=5(4.3)x | | -4+8b+b-2-6b-5+22=b-4b+30-2-3-b | | 19=2x-7 |